Jo March’s Effort for Equality in The Little Women Film: A Utilitarianism Perspective - Dias Nindya Subagiyo; Sumayah (University of Surakarta, 2025)
This study examines the character Jo March in Greta Gerwig’s Little Women (2019) from the perspective of John Stuart Mill’s utilitarianism, focusing on her actions to achieve equality, freedom, and collective happiness. The purpose of this study is to identify indicators of utilitarianism in Little Women from John Stuart Mill’s perspective, analyze how Jo March’s actions reflect the principles of utilitarianism, and investigate the underlying reasons and social implications of her utilitarian behavior, particularly in promoting meaningful happiness and social well-being. Using a qualitative analytical descriptive method, this study uses primary data from dialogues and film scenes, supplemented by secondary sources such as relevant literature and previous studies. The findings of this study reveal that Jo’s actions, such as establishing a school, writing to support her family, and advocating for gender equality, demonstrate actions and commitments to achieving equality, freedom, and collective happiness. This is in line with Mill’s principles of collective happiness, individual sacrifice, and freedom. Her decisions emphasize the importance of prioritizing the welfare of society while pursuing personal aspirations. This study contributes to literary and ethical discourse by offering a new perspective on Jo March as a moral agent who embodies utilitarian ideals, thereby expanding understanding of her character and the film's broader commentary on gender and social progress.